NILAI PENDIDIKAN KARAKTER DALAM NOVEL BULAN TERBELAH DI LANGIT AMERIKA - Lastaria, NFN; Widya, NFN (Balai Bahasa Kalimantan Tengah, 2019)
Character Education Values in Novel Month After the American Sky. Talking about novel issues and character values that a good novel is a novel that has many benefits or has many good values. Therefore, researchers chose the novel as a study material. Novels taken as study material are novels written by Hanum Salsabiela Rais and Rangga Almahendra with the title